Method Digital Learning for Increase Ability Early Childhood Literacy - Purnamasari, Lora (RADINKA JAYA UTAMA PUBLISHER, 2024)
One of the learning media is a digital fairy tale application available with pictures​ for download on the Google Play Store. The objective of this study is to learn in a way comprehensive how using digital learning media increases the ability of literacy children age early. Research quantitative This uses articles and journals accredited nationally as data sources and references. Research This in a way special see how digital learning media can help children Study literacy. Knowledge of letters, knowledge of sound letters, consciousness of phonemics, and comprehension of the concept of writing are indicators important to skills literacy. Digital applications that can be accessible to everyone, including teachers, parents, and students, used in the study This For looks for solutions for problem literacy. Study This is classified as in type study qualitative and using approach studies case. Analysis results study show that using learning media digital can also increase the skills and literacy child age early in PAUD institutions with give teachers the tools they need need for use it. Research This shows that tool digital learning can be used to increase ability literacy child age early PAUD institutions.